Instructional Policy and the Development of Instructional Computing: Maintaining Adaptive Educational Programs - Robert L. Blomeyer Jr. (Educational Considerations, 1986)
The potential benefits of microcomputer use in the schools are gains in efficiency, equity, and quality of the instructional programs.